Current Status of Self-transcendence among Lung Cancer Patients and Its Influencing Factors - Yang, Xue; Luo, Yu; Ye, Lijuan; Yu, Yingli; Zhu, Daxing (Zhongguo fei ai za zhi, 2024)
Different degrees of self-transcendence exist in lung cancer patients, which can stimulate patients' self-awareness and promote them to face negative events in life positively, thus improving patients' quality of life and treatment outcomes. However, there are few reports on self-transcendence in lung cancer patients in China, and the related influencing factors have not yet been clarified. This study aims to investigate the current situation of self-transcendence in lung cancer patients and explore its risk factors, so as to provide a theoretical basis for clinical intervention decision-making. 243 lung cancer patients who were admitted to the Department of Lung Cancer Center of West China Hospital, Sichuan University from September 2023 to February 2024 were enrolled as the study subjects; general information questionnaire, self-transcendence scale, Herth hope scale and social support scale were used for the investigation. The influencing factors related to self-transcendence of lung cancer patients were an